An Analysis of the Cultural Identities in the Bun Phawet Tradition of Non Rang Sub-District Community, Mueang Roi Et District, Roi Et Province - Pabhāto (Weingwiset) , Phramaha Phanuphong; Phrakhru Bhavanaphatthanabandit (Journal of Graduate Saket Review, 2025)
This research aims to 1) study the participation process of the Phawet Festival in Non Rang Sub-district, Mueang Roi Et District, Roi Et Province; 2) promote participation in the Phawet Festival in Non Rang Sub-district, Mueang Roi Et District, Roi Et Province; and 3) analyze the cultural identity of the Phawet Festival in Non Rang Sub-district, Mueang Roi Et District, Roi Et Province. Data were collected by interviewing 22 people involved, conducting group discussions, and conducting participatory practices. Data were analyzed using content analysis, and presented in a descriptive analysis. The research results showed that: 1) Phawet Festival in Non Rang Sub-district is divided into 5 parts: participation in planning and preparation, preparation of venue, preparation of food for merit-makers, participation in organizing activities, and determination of roles of community members. The participation behaviors are 4 types: participation in merit-making, helping with work, donation, and learning/dissemination. 2) The promotion of participation in the Phawet Festival in Non Rang Sub-district through 6 cooperation mechanisms: social and cultural mechanisms, economic mechanisms, political mechanisms, internal community mechanisms, network mechanisms, and community cost mechanisms. 3)The research results analyzed the cultural identity in the outstanding Bun Phawet tradition of the Non Rang Subdistrict community, which can be divided into 9 parts: inventions, eating, entertainment, the procession of Kanthok Kan Lon, making silver flower trees, dressing, singing, art, and cultural transmission, which is a pluralistic culture: (1) material culture, including creative things, equipment and tools, creative arts, technology, community products, symbols in Bun Phawet, and community lifestyles; (2) non-material culture, including beliefs, values, language, and performing arts in the Bun Phawet tradition.